Traction Performance Analysis of Three Models of Traction Device for Muddy Soil - Frandy Mey Syaputra; Wawan Hermawan; Radite Praeko Agus Setiawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Muddy paddy fields cause the traction performance of conventional traction devices to be suboptimal. Research on the analysis of traction performance on various traction devices is needed. The objective of this research is to design, analyze traction performance, and determine the best design from three models of traction devices, i.e. 1) track type, 2) pedal type, and 3) screw type on deep muddy soil. The research method used in this study is experimental, testing the traction performance of the three models at soil bin in muddy soil conditions at 25 cm deep. The parameters measured during the traction performance test are slip, sinkage, and traction efficiency. The treatment used in this study is a vertical load ranging from 93.2 N to 222.7 N. The best traction device design was chosen using the Analytical Hierarchy Process method. The results show that the traction performance achieved the highest score in determining the best traction device design, with a score of 0.78 (track) for the minimum load, 0.83 (track) for the medium load, and 0.87 (track) for the maximum load. Therefore, the track design was ideal, scoring the highest across all parameters.